Healthy work environment and nurses' competency towards the prevention of pressure ulcers in critically III patients. - Shrestha,Amrita (2017)
ABSTRACT: Competency of nurses plays vital role towards the prevention of pressure ulcers(PUs) in critically ill patients. The descriptive correlation study was conducted to examine the level of healthy work environment (HWE) the level of nurses competency, and the relationship between the HWE and nurses competency towards PU prevention in critically ill patients in Nepal. This study included 98 eligible intensive care unit (ICU) nurses from there referral central hospitals of Kathmandu, Nepal,during February to April 2017. The healthy work environment assessment tool with the Open Ended Questionnaire (OEQ) was used together to measure the HWE. The Nurses cometency towards PU prevention questionnaire with 3 subscales of knowledge, attitude, and practices was used to measure nurses competency towards PU prevention. The scale content validity index (S-CV) of the instruments was examined, yielding a S-CVI of 1.0. The reliability of the instruments were also examined, with Cronbach's alpha coefficients of 90 for the healthy work environment assessment tool, KP-20 coefficient of 7.0 for Nurses knowledge on PU prevention questionnaire, and Cronbach's alpha coefficicients of .70 and.73 for Nurses attitude on PU prevention questionnaire and Nurses practice on PU prevention questionnaire respectively. The descriptive statistical analysis of the study revealed a low level of the HWE(M=67.69,SD=13.58) and the overall nurses competency (M= 63.28,SD=6.59) towards PU prevention in critically ill patients. In this study, nurses knowledge was at a low level (M=65.66, SD= 11.20), attitude at a moderate level (M=77.74,SD=10.57), and the practice at a very low level (M=46.45, SD=7.08). Pearson's Product Moment Correlation analysis of the study finding revealed a statistically significant positive relationship (r=.28,p=.01) between the HWE and nurses competency towards PU prevention on critically ill patients. Developing and sustaining competent critical care nurses who have adequate knowledge, attitude and practice towards PU prevention under the healthy work environment in the critical care context are highly needed.